Determination and study of the eutectic point and the complex impedance of lead titanate (Latakia University Journal -Basic Sciences Series, 2022)
Lead titanate (PT) compounds doped with zirconium with the chemical formulaPbTi1-xZrxO3 (x=0.0,0.5,0.6,0.7,0.8,0.9) were prepared by the ceramic method where samples were calcined at 900o C for 4h. By using X-ray spectra (XRD) the formation of the required phases was confirmed. The substance was found in the tetragonal phase at a concentration x =0.0 and 0.5, While at concentrations x = 0.6, 0.7, 0.8 and 0.9, the phase shift begins from the tetragonal to the cubic phase. The eutectic point of the compound PT was also found, which reached T=1688K. The complex impedance of (PT) compound was studied at different temperatures and It was observed decreasing with increasing temperature.